EFL Instructors' Perceptions of Utilizing Mobile-Assisted Language Learning in Higher Education - Dağdeler Kübra Okumuş; Demiröz Hakan (Sciendo, 2022)
Introduction: One of the prominent approaches in language education is Mobile-Assisted Language Learning (MALL) due to recent advances in technology. To benefit from MALL effectively and develop it when it is required, it is important to know the perceptions of the ones who use it. Although much research related to students' and teachers' perceptions of MALL in primary and secondary education is present in the literature, research related to perceptions of instructors in higher education is limited. Thus, this study aimed at identifying the instructors' perceptions of utilizing MALL in higher education.